2020
DOI: 10.3390/w12020513
|View full text |Cite
|
Sign up to set email alerts
|

A Cone Fishway Facilitates Lateral Migrations of Tropical River-Floodplain Fish Communities

Abstract: Fisheries in many tropical river-floodplain systems are under threat from physical obstructions caused by ongoing river infrastructure development. There is a growing need for innovative, cost-effective technologies to mitigate the impacts of these obstructions. This study examined the effectiveness of a new cone fishway for facilitating lateral migrations of river-floodplain fish communities in the Lower Mekong Basin in Lao PDR. We assessed the species richness, size range, abundance and biomass of fish able … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…However, since VSFs generally require higher discharges to operate compared to pool-type fishways with bottom orifices and/or notches, operators may not share the same opinion, whereas they fail to meet one of the most challenging criteria in fishway design-the requirement to use as little water as possible for two main reasons: (i) construction costs are directly inflated with the design discharge; (ii) the more water volume is diverted, the less is available to hydropower production or other services provided by the dam, such as drinking water and irrigation [45]. Furthermore, in recent years, there has been a growing need to develop cost-effective fishways with lower turbulence that may operate with a broad discharge range [46]. In the present study, an experimental approach was conducted to assess entrance performance (entrance time and entry efficiency) and transit times of two Iberian cyprinids negotiating four distinct fishway configurations-using the same water depth in the pools-two VSFs and two MSFs, to gather insights about the fish passage behavior under different hydrodynamic scenarios and how conservation managers and dam operators may consider alternative mitigation cost-effective solutions capable of matching their goals.…”
Section: Discussionmentioning
confidence: 99%
“…However, since VSFs generally require higher discharges to operate compared to pool-type fishways with bottom orifices and/or notches, operators may not share the same opinion, whereas they fail to meet one of the most challenging criteria in fishway design-the requirement to use as little water as possible for two main reasons: (i) construction costs are directly inflated with the design discharge; (ii) the more water volume is diverted, the less is available to hydropower production or other services provided by the dam, such as drinking water and irrigation [45]. Furthermore, in recent years, there has been a growing need to develop cost-effective fishways with lower turbulence that may operate with a broad discharge range [46]. In the present study, an experimental approach was conducted to assess entrance performance (entrance time and entry efficiency) and transit times of two Iberian cyprinids negotiating four distinct fishway configurations-using the same water depth in the pools-two VSFs and two MSFs, to gather insights about the fish passage behavior under different hydrodynamic scenarios and how conservation managers and dam operators may consider alternative mitigation cost-effective solutions capable of matching their goals.…”
Section: Discussionmentioning
confidence: 99%
“…Since the mid-2000s, a multi-disciplinary research and development program in the Mekong Basin (summarized in Baumgartner et al, 2019a) has: documented the ubiquity of water management structures (Marsden et al, 2014); demonstrated methods for enabling fish to pass low-head barriers (Baumgartner et al, 2019b(Baumgartner et al, , 2020; outlined socio-economic benefits of improved fish passage (Millar et al, 2019); developed a decision making tool for assessing benefits-costs of fishways on low-head barriers (Cooper et al, 2019); and demonstrated scale-out of results through irrigation infrastructure rehabilitation projects in southern and northern Lao, funded by the World Bank and the Asian Development Bank, respectively (Baumgartner et al, 2019a). The program continues to generate data on the scaleout and cost-benefit of fishways to reconnect aquatic ecosystems in the Mekong, and more recently has initiated similar work in Myanmar and Indonesia.…”
Section: Investing In Ecological Offsets As An Alternative To Fishwaymentioning
confidence: 99%